Palladas and the Yale Papyrus Codex (P. CtYBR inv. 4000) - Kanellou, Maria,; Carey, Chris, (Papyrologica Lugduno-Batava ;, 2022)
The Yale papyrus codex has significantly enriched our knowledge of ancient Greek epigram, while it also sparked a lively debate around its date, authorship, and the interpretation of individual poems. This book offers the first collection of essays into this fascinating and elusive text.